Tafsir Alquran Bahasa Madura: Mengenal Tapsèr Sorat Yaa-siin (BhasaMadhura) Karya Muhammad Irsyad - Fawaidur Ramdhani; Ahmad Zaidanil Kamil (Nun : Jurnal Studi Alquran dan Tafsir di Nusantara, 2019)
This article points to review one the Quranic interpretationwritten by Muhammad Irsyad. This interpretation which he called Tapsèr Sorat Yaa-siin (Bha>sa Madhura>) almost disappear in the middle of the Quranic interpretationdiscussions in Indonesia. Basically, there is no much different to other ordinary interpretation, both in terms of writing, presentation of the systematic or the method used. This interpretation was written in Madurese language in the Latin script and typed by the typewriter. As for verses, written by handwriting. The method used in this interpretation is the maud}u>‘i@ surah method, while Surah Yasin as the focus of interpretation. Tapsèr Sorat Yaa-siin (Bha>sa Madhura>) has two nuances (type), those are the scientific and social type. During the interpretation process, Muhammad Irshad utilized the scientific perspective to uncover the scientific Quran and at the same time to respond several mythologies that is still rooted in Madurese society. According to Irsyad’s view, the Quran not only acts as a guide, but also as a source of all knowledge. It is not only sacred, but also scientific. Humans should use their minds to uncover scientific messages contained in the Quran.